Răspuns :
3×3+3×3=81..fals9+9=81
3×3×3×3=81..adevarat9×9=81
10×(24+24÷4)=300
10×(24+6)=300
10×30=300
300=300adevarat
43×2+243÷3=100÷4×0×8
86+81=25×0
167=0 fals
43×0×243÷3=100÷4×0×8
0×81=0
0=0
(100-36+3)×8=8×11
67×8=88
536=88 fals
100-36+3×8=8×11
64+24=88
88=88
2)3 ÷3+ 3÷ 3=2
3 ×3 +3 ×3=18
6 ×6 -6- 6=24
6- 6+ 6 ÷6=1
6 +6 +6 ÷6=13
3)5 5 5 5=70
5 5 5 5=49nu imi vine nici o inspiratie ma voi mai gandi
3×3×3×3=81..adevarat9×9=81
10×(24+24÷4)=300
10×(24+6)=300
10×30=300
300=300adevarat
43×2+243÷3=100÷4×0×8
86+81=25×0
167=0 fals
43×0×243÷3=100÷4×0×8
0×81=0
0=0
(100-36+3)×8=8×11
67×8=88
536=88 fals
100-36+3×8=8×11
64+24=88
88=88
2)3 ÷3+ 3÷ 3=2
3 ×3 +3 ×3=18
6 ×6 -6- 6=24
6- 6+ 6 ÷6=1
6 +6 +6 ÷6=13
3)5 5 5 5=70
5 5 5 5=49nu imi vine nici o inspiratie ma voi mai gandi
1)3·3+3·3=81(F)
3·3·3·3=81(A)
10·(24+24:4)=300(A)
43·2+243:3=100:4·0·8(F)
(43·2+243:3)·0=100:4·0·8(A)
100-36+3)·8=8·11(F)
100-(36-3·8)=8·11(A)
2)3·3-3:3=2
3·3-3·3=18
6+6+6+6=24
6-6+6:6=1
6:6+6+6=13
3)(5+5+5)·5-5=70
(5+5·5)-5:5=49
3·3·3·3=81(A)
10·(24+24:4)=300(A)
43·2+243:3=100:4·0·8(F)
(43·2+243:3)·0=100:4·0·8(A)
100-36+3)·8=8·11(F)
100-(36-3·8)=8·11(A)
2)3·3-3:3=2
3·3-3·3=18
6+6+6+6=24
6-6+6:6=1
6:6+6+6=13
3)(5+5+5)·5-5=70
(5+5·5)-5:5=49